Comparing Teachers’ English and Indonesian Questions in Classroom Interaction - Meisyani Gustri Fadila; Hamzah Hamzah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Classroom interaction is defined as an interaction in order to transfer the knowledge from teacher to students or sometimes exchange ideas between student to other students. In order to reach students’ understanding about the material, interaction between teacher and students are crucial. As the result, this research aimed to analyze and compare the teachers’ questioning in two languages, English and Indonesian. Then, it applied a qualitative descriptive method as a research design. There were six English teachers becoming the participant in this research. The research gathered the data through observation by using video recording as the instrument. After that, the video was transcribed and it analyzed based on Sidnell’s theory (2013). The result of this research presented most English teachers asked questions through target and local language and content question was the highest percentage in both languages’ questions. In questioning, teachers mostly presupposed on asking the lesson so that they applied topic agenda and the answer over non-answer response preference for all aspects of questioning.